An intervention to improve caregiver self-efficacy and contribution to self-care does not affect caregiver anxiety, depression, quality of life and sleep. Secondary outcome analysis of MOTIVATE-HF RCT. (2nd July 2022) - Locatelli, G; Rebora, P; Occhino, G; Ausili, D; Riegel, B; Vellone, E; Alvaro, R
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Center of Excellence for Nursing Scholarship (CECRI), Rome, Italy. Background: Caregiver contribution (CC) to self-care can improve patient outcomes in heart failure (HF). However, caring for a person with HF can be a burdensome experience for caregivers. Experimental studies aimed at improving caregiver self-efficacy and CC to HF self-care are scarce. Moreover, it is underexplored if interventions aiming to improve caregiver self-efficacy and CC to HF self-care consequently affect caregiver anxiety, depression, quality of life and sleep. Purpose: To evaluate if the delivery of a Motivational Interviewing intervention aimed at improving caregiver self-efficacy and CC to HF self-care affects caregiver anxiety, depression, quality of life, and sleep. Methods: Secondary outcome analysis of the MOTIVATE-HF randomized controlled trial. Participants were recruited from three centers in Italy, and they were randomized into three arms: Arm 1 (Motivational Interview for patients), Arm 2 (Motivational Interview for patients and caregivers), Arm 3 (standard care). The intervention consisted in one face-to-face MI session, plus three telephone contacts within two months from enrollment with patients (Arm 1) or with patients and caregivers (Arm 2). Data were collected at baseline and after 3, 6, 9, 12 months. Anxiety and depression were assessed using the Hospital Anxiety and Depression Scale, quality of life was measured with the 12-Item Short-Form Health Survey, and sleep was evaluated with the Pittsburgh Sleep Quality Index. Results: A total of 510 patient and caregiver dyads were enrolled. Caregiver median age ranged between 53 and 57, they were mainly female (76%), married (72%), spouses (37%), educated at high school or university level (55%), employed (73.5%), and living with the patient (60%). At baseline, anxiety, depression, quality of life and sleep scores were comparable among the three Arms. Over the year of follow-up, anxiety, depression, and sleep disturbances decreased, while quality of life slightly increased in all the three Arms. However, these changes were not significant in any of the study arms. When comparing these changes between Arm 2 and Arm 1 and 3, we did not observe any significant difference. Conclusion: Delivering Motivational Interview to caregivers to improve their self-efficacy and contribution towards patient self-care did not increase caregivers' own levels of anxiety and depression and did not decrease their quality of life and sleep. This may help tailoring future interventions for caregivers knowing that such an intervention does not worsen caregivers' conditions and wellbeing.